2022
DOI: 10.3171/2021.5.jns21310
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid for enhanced surgical visualization of high-grade gliomas: a prospective, multicenter study

Abstract: OBJECTIVE Greater extent of resection (EOR) is associated with longer overall survival in patients with high-grade gliomas (HGGs). 5-Aminolevulinic acid (5-ALA) can increase EOR by improving intraoperative visualization of contrast-enhancing tumor during fluorescence-guided surgery (FGS). When administered orally, 5-ALA is converted by glioma cells into protoporphyrin IX (PPIX), which fluoresces under blue 400-nm light. 5-ALA has been available for use in Europe since 2010, but only recently gained FDA approva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The 5-ALA application in the low-grade gliomas seems limited by low fluorescence visibility under the microscope, with a positive fluorescence rate ranging between 0 and 20 %. [ 55 , 56 ] Owing to the heterogeneity of glioma, the anaplastic foci within low-grade glioma, with no evidence of preoperative contrast enhancement on MR, could be detected intraoperatively. However, the general uptake of 5-ALA preoperatively in patients with low-grade glioma needs further studies for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-ALA application in the low-grade gliomas seems limited by low fluorescence visibility under the microscope, with a positive fluorescence rate ranging between 0 and 20 %. [ 55 , 56 ] Owing to the heterogeneity of glioma, the anaplastic foci within low-grade glioma, with no evidence of preoperative contrast enhancement on MR, could be detected intraoperatively. However, the general uptake of 5-ALA preoperatively in patients with low-grade glioma needs further studies for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The approval allows the use of ALA as an intraoperative imaging probe to facilitate tumor resection in patients with high-grade gliomas (grade III or IV) following a standard oral administration of 20 mg/kg body weight at about 3 h prior to anesthesia. A recently completed multi-center clinical study in the U.S. further confirmed that ALA is well-tolerated and possesses high sensitivity and positive predictive value as a tumor diagnostic agent for high-grade gliomas [ 49 ].…”
Section: Ala As An Intraoperative Imaging Probementioning
confidence: 99%
“…It can be less useful at discriminating non-tumoral brain in the in ltrative glioma margin since the uorescence signal is lower than in the bulk of the tumor. Despite a high sensitivity and positive predictive value for detecting tumor, speci city and negative predictive value is lower with 5-ALA. 23,24 Hollon et al 25 showed stimulated Raman histology (SRH) could be used on brain biopsy specimens to diagnose brain tumor types. This technique is a form of stain-free, deep learning-based histology that has the potential to replace frozen section histopathologic analyses.…”
Section: Mainmentioning
confidence: 99%